2020
DOI: 10.1021/acsanm.0c00842
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic-Framework-Derived N-, P-, and O-Codoped Nickel/Carbon Composites Homogeneously Decorated on Reduced Graphene Oxide for Energy Storage

Abstract: In this work, a type of high-performance electrode material of Ni/C/rGO-n [n = wt % of reduced graphene oxide (rGO)] derived from nickel-based metal−organic framework (Ni-MOF) for supercapacitors is successfully prepared. First, a hydrogen-bonding-assisted approach to continuous growth of Ni-MOFs on graphene oxide (GO) sheets is developed through the application of a hexadentate ligand, hexakis(4-carboxylphenoxy)cyclotriphosphazene (CTP-COOH), as the anchor with multiple biting points. The thicknesses of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The synergistic effect between different heteroatoms is conductive to good electrochemical behavior, including a large charge storage capacity (1258.7 F g −1 at 8 A g −1 ), excellent rate performance (1087.1 F g −1 at 20 A g −1 ), and superior cycling stability (110% after 50 000 cycles). [ 68 ] In another example, a Zn‐MOF constructed with 2‐ethylimidazole and 5‐methyltetrazole as a double ligand was chosen as the precursor for the preparation of a ultrahigh‐content (14.23 wt%) nitrogen‐decorated nanoporous carbon, demonstrating that pyridinic N and pyrrolic N play an important role in pseudocapacitance. [ 69 ] Generally, the nitrogen content of carbon materials is related to calcination temperatures.…”
Section: Supercapacitor Applicationsmentioning
confidence: 99%
“…The synergistic effect between different heteroatoms is conductive to good electrochemical behavior, including a large charge storage capacity (1258.7 F g −1 at 8 A g −1 ), excellent rate performance (1087.1 F g −1 at 20 A g −1 ), and superior cycling stability (110% after 50 000 cycles). [ 68 ] In another example, a Zn‐MOF constructed with 2‐ethylimidazole and 5‐methyltetrazole as a double ligand was chosen as the precursor for the preparation of a ultrahigh‐content (14.23 wt%) nitrogen‐decorated nanoporous carbon, demonstrating that pyridinic N and pyrrolic N play an important role in pseudocapacitance. [ 69 ] Generally, the nitrogen content of carbon materials is related to calcination temperatures.…”
Section: Supercapacitor Applicationsmentioning
confidence: 99%
“…Shi et al [ 78 ] found N, P and O co-doped Co/C composites derived from Co-hexa-(4-carboxyl-phenoxy)-cyclotriphosphazene (CTP-COOH, containing C, N, O and P) can reach a maximum of 739.6 F g −1 in 6 M KOH at a current density of 1 A g −1 and keep the capacitance retention of 80.6% over 5000 cycles. Latterly, they [ 79 ] took the same organic linker, CTP-COOH, but a different salt of Co to prepare binder-free MOFs-derived carbon as a supercapacitor electrode. They [ 79 ] claimed that the electrochemical properties of MOF-derived-C/rGO (using GO as the MOFs growth template) composites are greatly enhanced compared to bare MOF-derived C. Among the obtained Ni/C, Ni/C/rGO-x (x = 2, 4 and 8 wt%), Ni/C/rGO-4 (GO: 4 wt%) exhibits the best electrochemical performance, with a maximum capacitance of 1258.7 F g −1 at a current density of 8 A g −1 and magnificent stability with capacitance retention of 110% over 50,000 cycling tests.…”
Section: Mofs As Precursors For Scsmentioning
confidence: 99%
“…Latterly, they [ 79 ] took the same organic linker, CTP-COOH, but a different salt of Co to prepare binder-free MOFs-derived carbon as a supercapacitor electrode. They [ 79 ] claimed that the electrochemical properties of MOF-derived-C/rGO (using GO as the MOFs growth template) composites are greatly enhanced compared to bare MOF-derived C. Among the obtained Ni/C, Ni/C/rGO-x (x = 2, 4 and 8 wt%), Ni/C/rGO-4 (GO: 4 wt%) exhibits the best electrochemical performance, with a maximum capacitance of 1258.7 F g −1 at a current density of 8 A g −1 and magnificent stability with capacitance retention of 110% over 50,000 cycling tests. This is partially attributed to the increased surface area of Ni/C/GO-4 nanosheets (126.4 m 2 g −1 ), compared to the bare Ni/C synthesized without the presence of GO with surface area of 3.7 m 2 g −1 .…”
Section: Mofs As Precursors For Scsmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] Building on this, MOFs have been widely used as precursor materials for the generation of carbon materials hybridized with nanoscale metals and metal oxides and were used in a variety of different energy-related applications, including electrocatalytic oxygen evolution reaction/hydrogen evolution reaction, supercapacitors, and batteries. [43][44][45][46][47] Herein, we report a facile strategy for the in situ synthesis of ultrafine anatase TiO 2 nanoparticle encapsulated hierarchical nitrogen-rich graphitic carbon ( -bdc linkers and features tetrahedral and octahedral cages (6.13 and 12.55 Å) with accessible pore windows of 5-7 Å (Scheme 1). [42] We took advantage of its intrinsic porous structure to build an efficient anode material for a KIB.…”
Section: Introductionmentioning
confidence: 99%